Optimizing State-Owned Asset Management at the Sekupang Domestic Passenger Terminal Under Batam Port Authority in Riau Islands - Amirsyah, Mochamad Badrudjamal; Rahmat Hidayat; Agus Susanto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to analyze the management of BMN assets in 2022 and formulate a strategy for optimizing assets based on commercialization. This study uses a descriptive qualitative approach with data collection through semi-structured interviews. Data collection involved 11 (eleven) internal and external sources through purposive sampling, including the Director of Evaluation of BP Batam, Terminal General Manager, Head of UAKPB, and tenants. Data analysis was carried out through reduction, presentation, and drawing conclusions, as well as integrating SWOT-TOWS analysis strengthened by triangulation. The results of the study indicate that the management of BMN assets in BUP Batam is still hampered by cultural factors, training, innovation incentives, as well as centralized bureaucracy and authority. The best strategy for optimizing the Sekupang Terminal is the S-O Strategy which relies on strategic location, modern infrastructure, and pro-business policies to encourage the commercialization of public assets. BP Batam is advised to implement a market demand-based strategy, such as tenant cooperation, retail zone development, and premium services. In addition, the government needs to establish a more flexible asset management policy to increase efficiency, attract private investment, and balance regulations with optimization of income and social benefits. This commercialization strategy is expected to increase the productivity of Sekupang Terminal, strengthen fiscal independence, and create broader economic and social impacts. Keywords: State-Owned Goods (BMN), Commercialization, Asset Optimization, Regulation, HR